1972
DOI: 10.1136/gut.13.7.544
|View full text |Cite
|
Sign up to set email alerts
|

Observations on folate absorption with particular reference to folate polyglutamate and possible inhibitors to its absorption

Abstract: SUMMARY A test system for detection of inhibitors to the enzyme which removes the glutamic acid peptide chain from folate polyglutamates (folate conjugase) is described. This utilizes the reaction between plasma conjugase and the folate polyglutamate in red blood cell haemolysate. Diphenylhydantoin and yeast extracts did not inhibit plasma conjugase.The better absorption of monoglutamate forms of folate as compared to polyglutamate forms was confirmed. Polyglutamates were absorbed normally by patients with per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…It has been reported that sulfobromophthalein and 4,4Ј-diisothiocyanostilbene-2,2Ј-disulfonic acid are inhibitors of pH-sensitive folate transport in the small intestine (Perry and Chanarin, 1972;Schron et al, 1985). Consistent with that, we found that both of them inhibit folate transport mediated by hPCFT/HCP1 significantly (Fig.…”
supporting
confidence: 80%
“…It has been reported that sulfobromophthalein and 4,4Ј-diisothiocyanostilbene-2,2Ј-disulfonic acid are inhibitors of pH-sensitive folate transport in the small intestine (Perry and Chanarin, 1972;Schron et al, 1985). Consistent with that, we found that both of them inhibit folate transport mediated by hPCFT/HCP1 significantly (Fig.…”
supporting
confidence: 80%
“…Malabsorption of folate has been reported to occur (4-6) but has not been confirmed (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In persons with normal folate levels, phenytoin is unable to depress the intestinal ab sorption of folic acid [18]. Once established, folate deficiency may cause alterations in the intestinal mucosa morphology and function [3], and this gastrointestinal dysfunction may be corrected by parenteral folic acid alone [8].…”
Section: Discussionmentioning
confidence: 99%